Hard light : a Cass Neary crime novel - Hand, Elizabeth (Cass Neary., 2016)
"As her passionately devoted fans know, Elizabeth Hand is a uniquely gifted storyteller. Her iconoclastic series of crime novels which features offbeat photographer Cass Neary, began with the underground classic Generation Loss, and that was followed by the brilliant Available Dark. Katherine Dunne, author of Geek Love, describes Cass as "one of literature's great noir antiheroes," and comparisons to Stieg Larsson's Liz Salander abound. As the story opens, Cass arrives in London where she meets and is reunited with her long-lost lover, Quinn O'Boyle, who is wanted by both Interpol and the Russian mob. When Quinn then fails to show at their rendezvous point, Cass is fearful she'll be the next to disappear, and she goes on the run"--